Analisis Risiko Teknologi Informasi Berbasis Risk Management Menggunakan Kerangka Kerja OCTAVE-S Pada Unit Pengelola Sistem Informasi Dan Kehumasan (PSIK) Fakultas Ilmu Komputer Universitas Brawijaya - Via Aprilia Prabawati; Aditya Rachmadi; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Fakultas Ilmu Komputer Universitas Brawijaya is one of the faculties that has implemented and developed information technology in every its business process activity. Each activity related to information system development is handled by the Unit Pengelola Sistem Informasi dan Kehumasan (PSIK) Fakultas Ilmu Komputer. Although they have used a more computerized and integrated information system in conducting their duties and functions, they have never taken a risk assessment or implemented risk management. Based on the problem, solutions are provided to carry out the process of measuring and managing risk using the OCTAVE-S framework. The process is implemented by identifying and analyzing risk threats found in the Unit Pengelola Sistem Informasi dan Kehumasan (PSIK) Fakultas Ilmu Komputer, which will then be used to provide mitigation recommendations in accordance with security practices. The results of this study found 3 security practice areas that have yellow stoplight status and 1 security practice area that have red stoplight status. The four areas of security practice were then selected as mitigation areas.